Discovery of a Symptomatic Left Anomalous Coronary Artery from the Opposite Sinus and Postoperative Considerations - Ahmad Slim; John Thurlow; Jennifer Blevins; Shaun Martinho; Brian Markelz (Case Reports in Medicine)
This is the case of an 18 year old active duty soldier with symptoms of exertional chest pressure and syncope who was found to have anomalous origin of the left main coronary artery (LMCA) from the right coronary cusp (RCC) traveling partially between the great vessels before taking a septal approach between the left ventricular outflow tract (LVOT) and the right ventricular outflow tract (RVOT). Anomalous origin of coronary arteries is a rare condition that carries an increased risk of angina, myocardial ischemia, and sudden cardiac death (SCD). Surgical treatment of such anomalies with both high and lower risk features can be challenging, and traditional benefit from surgical correction may not be achieved due to complex anatomy. As evident by our patient, this rare condition even though benign from sudden death standpoint could be debilitating despite best efforts and available resources.